Luther's Doctrine of Vocation - Watson, Philip S. (Scottish journal of theology, 1949)
“Vocation” is a word of varied significance, both secular and religious. Religiously, it can mean God's calling of men into His kingdom through the proclamation of the Gospel, or His calling of particular persons to particular spheres of service such as the Ministry. Secularly, it can mean any trade, profession, or employment that a man may follow, including such occupations as the Ministry. The Latin original of the word, vocatio, and its German equivalent, Beruf, are used in all these senses by Luther, but with important differences. In the first place, the distinction between religious and secular is entirely foreign to his thinking. When he speaks of weltlicher Beruf, or “worldly vocation”, he never thinks of it as either irreligious or non-religious, but as a Divine appointment for our life in this world. In the second place, his conception of vocation includes a great deal more than ours normally does. In one of his sermons he raises the question, what it means to have a vocation. He answers it by saying: You are in a Stand, “station”, you are a married man or woman, a son or daughter, a man-servant or maid-servant; and he goes on to point out what duties such “stations” impose upon us, so that we had four heads and ten hands we should still have quite enough to do. Other lists bf “stations”—or “offices”, as he also calls them—include: the prince, the magistrate, the teacher, the scholar, the father, mother, children, master, servant, and many more.